Comparing Evidence‐Based Practice Competencies, Adoption, Barriers, and Predictors Among Nurses and Other Healthcare Professionals Across the Eastern Mediterranean Region. - Youssef, Naglaa; Gebreal, Assem; Saleeb, Marina; Alanazi, Alaa; Shepherd, Ashley; Al Asaad, Saja Hasan; Al Houri, Hasan Nabil; Tookhy, Nazir Ahmad; Shakhes, Shoaib Ahmad; Nawwar, Ahmed Essam; Warda, Nada Hossam Aly; Alhamdan, Hamza Ismail; et al. (Worldviews on Evidence-Based Nursing (John Wiley & Sons, Inc.), 2026)
Background: Current research lacks a comprehensive understanding of evidence‐based practice (EBP) adoption and its predictors across diverse healthcare professionals (HCPs) in the Eastern Mediterranean Region (EMR), particularly with a direct comparison between nurses and other professional groups. Objectives: This study aims to evaluate the EBP competencies, adoption levels, identified barriers, and associated predictors among nurses and other healthcare professionals (HCPs) within the EMR. Methods: A cross‐sectional, correlational, and comparative design was used. An electronic survey was distributed (April 27th–August 17th, 2023) via convenience/snowball sampling, inviting nurses, physicians, physiotherapists, dentists, and pharmacists across the EMR to complete the survey. Multivariate regression analysis and structural equation modeling (SEM) were used to identify predictors of EBP adoption. Results: A total of 4673 HCPs participated and reported several barriers to EBP adoption, including time constraints, difficulties in interpreting statistics, lack of authority to change practices, and insufficient equipment. Nurses had fewer postgraduate degrees but more work experience and full‐time employment than other HCPs. Despite reporting more workplace EBP support, nurses read less research, had lower EBP scores and adoption propensity, and perceived greater barriers than other HCPs (p < 0.002). Multivariate regression showed the highest barrier scores in Syria/Tunisia and the lowest in the United Arab Emirates. Nurses reported significantly higher barriers compared to other HCPs (p < 0.001). Fear of Change was not a primary barrier overall, but was elevated in specific subgroups of nurses. SEM showed good fit: RMSEA = 0.077, SRMR = 0.053, CFI = 0.80, χ2(df) = 917, p < 0.001. SEM showed that EBP adoption propensity and fear of change significantly mediate the relationship between HCPs' characteristics and EBP scores. Linking Evidence to Action: Despite having a positive attitude and propensity towards EBP, nurses lack the necessary knowledge and support to adopt it, and they face more barriers than other healthcare professionals. Nurses require greater support from healthcare leaders to enhance their EBP competencies and address the reported barriers. Policymakers and organizations should prioritize tailored, role‐specific training and supportive structures and environments to ensure equitable and effective EBP implementation for improving patient outcomes across the EMR.